2021
DOI: 10.3390/nu13061956
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum Therapy for Human Gastrointestinal Health and Disease

Abstract: There is increasing awareness that a broad range of gastrointestinal diseases, and some systemic diseases, are characterized by failure of the mucosal barrier. Bovine colostrum is a complex biological fluid replete with growth factors, nutrients, hormones, and paracrine factors which have a range of properties likely to contribute to mucosal healing in a wide range of infective, inflammatory, and injury conditions. In this review, we describe the anatomy and physiology of the intestinal barrier and how it may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 101 publications
(111 reference statements)
0
23
0
Order By: Relevance
“…On the prebiotic side, studies have shown that dietary supplementation of several different prebiotics exert beneficial effects in IBD through changes in the intestinal microflora composition, i.e., increasing beneficial bacteria such as Bifidobacteria and Lactobacilli and improving the intestinal epithelial barrier [70]. Bovine colostrum, for example, has repeatedly been shown to (i) inhibit gut pathogens while stimulating the growth of a healthy microbiota (the so-called eubiotic effect) [71][72][73], (ii) reduce iatrogenic injury to the gut [74], (iii) prevent and limit diarrhoea of different origins [74,75].…”
Section: Dysbiosis and Possible Dietary Interventionsmentioning
confidence: 99%
“…On the prebiotic side, studies have shown that dietary supplementation of several different prebiotics exert beneficial effects in IBD through changes in the intestinal microflora composition, i.e., increasing beneficial bacteria such as Bifidobacteria and Lactobacilli and improving the intestinal epithelial barrier [70]. Bovine colostrum, for example, has repeatedly been shown to (i) inhibit gut pathogens while stimulating the growth of a healthy microbiota (the so-called eubiotic effect) [71][72][73], (ii) reduce iatrogenic injury to the gut [74], (iii) prevent and limit diarrhoea of different origins [74,75].…”
Section: Dysbiosis and Possible Dietary Interventionsmentioning
confidence: 99%
“…This Special Issue of Nutrients , “The Use of Bovine Colostrum in Medical Practice and Human Health” contains five review articles covering various aspects of the potential use of BC, including its main constituents and uses [ 1 ], use in gastrointestinal health and disease [ 2 ], sports nutrition [ 3 ], pediatrics [ 4 ], and immune support [ 5 ]. It also includes a systematic review of its clinical use [ 6 ] and an original research article examining its effects on enteric bacteria [ 7 ].…”
mentioning
confidence: 99%
“…Several growth-factor constituents of BC elicit pro-proliferative (growth) and protective effects when tested in cell lines and in in vitro gastrointestinal models, suggesting relevance for maintaining gut integrity or stimulating repair. The article by Chandwe and Kelly [ 2 ] discusses the evidence regarding the potential value of BC for gastrointestinal conditions and is also covered in the systematic clinical review by Guberti [ 6 ] and, in relation to the use of BC to maintain gut integrity of athletes, in the article by Davison [ 3 ]. At least on a theoretical basis, one would expect this application to be one of the most optimistic, as the constituents of BC are able to directly interact with luminal pathogens, influence the gut microbiome and allow growth factors and cytokines direct access to the intestinal mucosa.…”
mentioning
confidence: 99%
See 2 more Smart Citations